Method for producing mixed-phase excited gypsum by wet-process phosphoric acid process as well as product and application thereof
By adjusting the ratio of phosphate ore powder, concentrated sulfuric acid and low-temperature mixed acid in the wet phosphoric acid process, performing solid-liquid separation and transformation treatment, the problem of high phosphorus and fluorine content in phosphogypsum is solved, and low-cost harmlessness is achieved Chemical treatment and efficient recycling of phosphorus resources are suitable for the production and promotion of building materials.
Patent Information
- Application Number
- CN202411531469.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-07
AI Technical Summary
The existing wet phosphorus and fluorine content in phosphogypsum products is high, making it difficult to achieve harmless treatment, and the production cost is high, which limits its application scope and efficiency.
A method of producing mixed-phase excitation gypsum is adopted by a wet phosphoric acid process. By adding phosphate powder, concentrated sulfuric acid and low-temperature mixed acid to the wet phosphoric acid extraction tank, solid-liquid separation and crystallization treatment are carried out, and the temperature and component ratio are controlled. A mixed phase stimulation gypsum with low phosphorus and low fluorine is obtained, and waste heat is used to save energy and reduce emissions.
The harmless treatment of phosphogypsum has been achieved, the phosphorus and fluorine content has been reduced, the activity and stability of gypsum has been improved, production costs have been reduced, and it is suitable for large-scale replacement and promotion of building materials, and the recovery rate of phosphorus resources has been improved.
Smart Images

Figure CN119263233A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wet-process phosphoric acid, and in particular to a method for producing mixed-phase activated gypsum by a wet-process phosphoric acid process, and a product and application thereof. Background Art
[0002] Wet-process phosphoric acid process: There are two methods for producing phosphoric acid, thermal phosphoric acid and wet-process phosphoric acid. The thermal phosphoric acid production process is mainly a process in which yellow phosphorus obtained by electrothermal method is burned in excess air to produce phosphoric acid. It has the disadvantages of high production energy consumption and serious impact on the environment. The wet-process phosphoric acid production process is mainly to use various inorganic acids to decompose phosphate ore to produce phosphoric acid. Its main inorganic acids include sulfuric acid, hydrochloric acid, and nitric acid. At present, the mainstream companies producing wet-process phosphoric acid use sulfuric acid as the extraction acid to decompose phosphate ore to prepare wet-process phosphoric acid. When sulfuric acid decomposes phosphate ore, it can be divided into 5 processes according to the different hydration forms of the generated CaSO4 crystals: one-step dihydrate method, one-step half-water method, half-water dihydrate method, dihydrate and half-water method, and dihydrate anhydrous method.
[0003] ① The one-step dihydrate process is relatively mature, with a wide process operation range, relatively stable production, and low difficulty in water balance control. It can be directly produced from phosphate rock, and has good adaptability to the ore. At present, more than 80% of my country's wet-process phosphoric acid adopts the one-step dihydrate phosphoric acid process. The dihydrate process can only produce dilute phosphoric acid with w(P2O5)=20%~25%. Filtration and washing are easy to operate and control. Before being used in the production of phosphate fertilizers, a dilute phosphoric acid concentration process needs to be added. However, the crystal fineness distribution of phosphogypsum produced by the dihydrate process is uneven. When distributing the slurry in the early stage of filtration, a large amount of phosphogypsum fine crystals penetrate the filter cloth and enter the finished phosphoric acid. The excess coefficient of sulfuric acid is high, resulting in a decrease in the quality of dilute phosphoric acid. The P2O5 extraction rate in phosphate rock is low, and the amount of non-water-soluble residual phosphorus in phosphogypsum is high. The by-product becomes phosphogypsum with a phosphorus content of 0.8-1.2%. It is generally used as solid waste. Its treatment is one of the most troublesome problems in the world and in China, and it is mainly stored in China.
[0004] ② The one-step semi-water process can produce high-concentration phosphoric acid with w(P2O5)=40%~45%, which can be directly used in the production of phosphate fertilizers, and has low energy consumption. The steam consumption per ton of P2O5 can be reduced by 1.2~1.7t compared with the dihydrate, saving 20%~27% of electricity consumption. The construction investment is low, which can be reduced by 14%~17% compared with the dihydrate process. The quality of phosphoric acid is good, which is convenient for further purification of wet phosphoric acid. However, the extraction rate of phosphate ore in the semi-hydrate process is low, generally only 92%~94%, and the quality requirements of phosphate ore are high. The water balance control is difficult, and only dry grinding can be used, which increases the cost of ore processing. The filtering and washing operations are difficult. The properties of phosphogypsum are unstable and in the metastable zone, which is not convenient for subsequent treatment. The operating rate is low, the equipment and pipelines are seriously blocked by fouling, and the cleaning is frequently stopped. The phosphorus content of semi-hydrate gypsum is 1.2-1.7%, and its treatment is also a headache. It is generally difficult to use as a building material and can only be used as a mine filling or environmental remediation material.
[0005] ③ The characteristic of semi-water-dihydrate wet phosphoric acid is that calcium sulfate is first formed into semi-hydrate crystals, and then hydrated and recrystallized into dihydrate. The production process of the concentrated acid process of the semi-water-dihydrate method with two filtrations can generally be divided into four main processes: semi-hydrate reaction, semi-hydrate filtration, semi-hydrate recrystallization and filtration. The advantage of this method is that after the first filtration, the semi-hydrate slurry can directly obtain concentrated phosphoric acid with a concentration of 40-45% P2O5, the total yield of P2O5 is high, and the quality of gypsum has been further improved; the disadvantage is that the whole process is filtered twice, especially the semi-hydrate filtration is difficult, the production is difficult to control, the operating rate is low, the quality requirements of the phosphate rock are high, and the investment is large. The main process was developed by a Japanese company, and there is no such process in China.
[0006] ④ The essence of the dihydrate and semi-hydrate method is to use dihydrate gypsum as raw material, and prepare it into semi-hydrate gypsum while removing the phosphorus and fluorine elements. For example, patent CN105174760B is a method for preparing α-semi-hydrate gypsum from dihydrate gypsum. Dihydrate gypsum and a crystal control agent are added to a mixed acid aqueous solution containing sulfuric acid and phosphoric acid to carry out a crystallization reaction, and the solid and liquid are separated. A part of the liquid phase returns to the crystallization tank to continue the crystallization reaction, and the other part is transported to the acid decomposition tank of sulfuric acid decomposition phosphate ore to produce phosphoric acid for utilization; the solid phase is washed with washing water, and the washing water is introduced into the above-obtained liquid phase for utilization. The solid phase obtained by washing can be dried into α-semi-hydrate gypsum powder, or it can be directly added with water without a drying step to make gypsum products such as gypsum boards, gypsum blocks, and gypsum components.
[0007] ⑤ The essence of the dihydrate anhydrous method is to use dihydrate gypsum as a raw material, and remove the phosphorus and fluorine elements from it to prepare it into anhydrous gypsum. For example, patent CN113772709B is a method for preparing anhydrous micron calcium sulfate using phosphogypsum. Water, acid, nucleating agent and crystal form control agent are added to phosphogypsum and heated to react, and then filtered and dried to obtain micron-grade anhydrous calcium sulfate. Its core is mainly sulfuric acid, and the acid can be sulfuric acid, or a mixture of sulfuric acid and any one of phosphoric acid, hydrochloric acid and nitric acid.
[0008] Therefore, improving the wet phosphoric acid process to reduce the phosphorus and fluorine content in its phosphogypsum products, meet the standards for harmless treatment of phosphogypsum and improve its properties and application scope is still the key research object of the current wet phosphoric acid process. It is necessary to study a method that can directly graft and transform in the wet phosphoric acid process, and use the original wet phosphoric acid equipment, process and heat to obtain new and better phosphogypsum products. Summary of the invention
[0009] In order to solve the above technical problems existing in the prior art, the present invention provides a method for producing mixed-phase activated gypsum by a wet phosphoric acid process.
[0010] A method for producing mixed-phase activated gypsum by a wet phosphoric acid process, specifically comprising the following steps:
[0011] (1) adding phosphate rock powder, concentrated sulfuric acid, low-temperature mixed acid, and filtrate to a wet phosphoric acid extraction tank; the mass ratio of phosphate rock powder: concentrated sulfuric acid: low-temperature mixed acid and filtrate is 1: (0-0.3): (1-5): (0.5-3); the reaction temperature of the extraction tank is adjusted to 50-90° C., reacting for 30-60 minutes, and obtaining phosphoric acid extraction slurry A;
[0012] (2) The slurry A in step (1) is subjected to solid-liquid separation to obtain a solid phase B and a clear liquid C, the clear liquid C is entered into an acid reservoir as a finished phosphoric acid, and the solid phase B, high temperature crystallization filtrate F, concentrated sulfuric acid, and a crystal form control agent are entered into a crystallization tank; the temperature of the crystallization tank is controlled to be 80-105° C., and the crystallization is performed for 2-10 hours to obtain a slurry D; wherein the mass ratio of each component is: solid phase B: high temperature crystallization filtrate F: concentrated sulfuric acid: crystal form control agent = 1: (0.8-5): (0.01-0.50): (0.01-0.6); the P2O5% content in the filtrate F is 3-16%, and the crystal form control agent is 1.0-5.0%.
[0013] (3) The slurry D in step (2) is subjected to solid-liquid separation to obtain a low-temperature crystallization filtrate F and a solid phase, and the solid phase is washed with washing water to obtain a solid phase E and a washing liquid G; the solid phase E is dried to obtain a mixed-phase activated gypsum or is directly used for subsequent gypsum product processing without drying.
[0014] Furthermore, the fineness of the phosphate rock powder in step (1) is 80-100 mesh, and the P2O5 content contained therein is 10-40%.
[0015] Furthermore, the mass fraction of the concentrated sulfuric acid in step (1) is 93-98%.
[0016] Furthermore, the low-temperature mixed acid in step (1), wherein the sulfuric acid concentration is 40-70% and the P2O5% concentration is 0.5-5%, can be recycled using the low-temperature mixed acid H, or can be directly prepared; the low-temperature mixed acid H is a mixture of the washing liquid G of the mixed-phase activated gypsum and concentrated sulfuric acid, which are mixed in a tubular reactor to obtain a high-temperature mixed acid H, and the high-temperature mixed acid H enters a heat exchanger to obtain a low-temperature mixed acid H, and the low-temperature mixed acid H enters an extraction tank for recycling.
[0017] Furthermore, the filtrate in step (1), wherein the P2O5% content is 3-16% and the crystal form control agent is 1.0-5.0%, can be recycled using the low-temperature crystallization filtrate F, or can be directly prepared.
[0018] Furthermore, the high-temperature filtrate in step (2), wherein the P2O5% content is 3-16% and the crystal form control agent is 1.0-5.0%, can be obtained by using the low-temperature crystal transformation filtrate F to enter a dedicated heat exchanger to obtain the high-temperature crystal transformation filtrate F, or can be obtained by direct configuration.
[0019] Furthermore, the crystal form control agent is a combination of four components: iron oxide, aluminum oxide, magnesium oxide, and fluorosilicic acid, and its total mass accounts for 2.0-8.0% of the crystal transformation filtrate components, wherein the iron oxide content is 0.2-0.3%, aluminum oxide is 0.4-2.0%, magnesium oxide is 0.5-4.0%, and fluorosilicic acid is 0.9-4.0%.
[0020] Furthermore, the method further comprises step (4): adding concentrated sulfuric acid to the washing liquid G in step (3) in a tubular reactor to dilute and release heat to obtain a high-temperature mixed acid H, and the high-temperature mixed acid enters a dedicated heat exchanger for heat exchange to obtain a low-temperature mixed acid H which enters an extraction tank for recycling. The sulfuric acid concentration in the mixed acid H is 40-70%, and the P2O5% concentration is 0.5-5%.
[0021] Furthermore, the method also comprises step (5): the low-temperature crystallization filtrate F of step (3) is fed into a dedicated heat exchanger to obtain a high-temperature crystallization filtrate F, and the high-temperature crystallization filtrate F is fed into a crystallization tank for recycling.
[0022] Furthermore, the composition of the washing liquid G is P2O5%, which accounts for 1-8% of the total mass of the washing liquid G, and SO4 2- It accounts for 2-8% of the total mass of lotion G.
[0023] The above method is a new process for reducing phosphogypsum emissions at the source. The improvement of the wet phosphoric acid process can be directly grafted and transformed in the wet phosphoric acid process and directly applied in the wet phosphoric acid process. The technical difficulty is low and large-scale production can be achieved in the wet phosphoric acid process. The original wet phosphoric acid equipment, process and heat are fully utilized, so the production cost is low, which is conducive to the large-scale replacement and promotion of building raw materials.
[0024] The mixed phase activated gypsum prepared by the above method and its application in the preparation of building materials products. The finally obtained mixed phase activated gypsum has good activity. In the liquid phase wet-based state, the performance can remain stable for a long time, and it will not hydrate and agglomerate for 16-40 hours, which can reduce the scaling and agglomeration problems of the process filtration and transportation system; and after adding an activator, a highly active building material product can be obtained, and the wet-based product can be directly used for processing building materials, or it can be dried into powder and then activated to process gypsum blocks, gypsum strips, gypsum-based self-leveling mortar and other products.
[0025] Compared with the prior art, the technical effects created by the present invention are embodied in:
[0026] 1. The present invention provides a novel method for preparing mixed-phase activated gypsum by a novel wet phosphoric acid process, which is an improvement on the traditional wet phosphoric acid process and can realize harmless treatment of phosphogypsum at low cost. The mixed-phase activated gypsum can maintain stable performance for 16-40 hours after being produced from the washing system end, and the transmission system will not cause scaling. After adding the activator, it can quickly recover its activity, and has superior performance in the subsequent drying process and direct processing of gypsum products by wet-based products. In addition, the dilution heat of concentrated sulfuric acid is fully utilized to complete high-temperature liquid phase cooling and low-temperature liquid phase heating, thereby saving energy and reducing emissions.
[0027] 2. The present invention has developed a new idea for harmless treatment of phosphogypsum: The treatment of phosphogypsum solid waste is a world problem. This new technology can provide a new idea for solving this world problem, and convert dihydrate phosphogypsum into a useful gypsum cementitious material - mixed phase activated gypsum in a liquid phase mixed acid system. The total phosphorus of the obtained mixed phase activated gypsum is less than 0.2%, the water-soluble phosphorus is less than 0.1%, and the water-soluble fluorine is less than 0.1%, which meets the national standard for harmless treatment. It is a new process for reducing phosphogypsum emissions at the source.
[0028] 3. The process of the present invention can be mass-produced: the improvement of the wet phosphoric acid process of the present technology can be directly grafted and converted in the wet phosphoric acid process, with low difficulty in industrialization, large-scale production can be achieved, and the original wet phosphoric acid equipment, process and heat can be utilized, so the production cost is low, which is conducive to the large-scale replacement and promotion of building raw materials.
[0029] 4. The final mixed phase activated gypsum of the present invention is composed of: anhydrous phase accounts for 40%-60%, semi-aqueous phase accounts for 15-30%, and dihydrate phase accounts for 3-20%. The content of impurities (harmful components phosphorus and fluorine) in the product is very low: the total phosphorus in the obtained product is less than 0.2%, the water-soluble phosphorus is less than 0.1%, and the water-soluble fluorine is less than 0.1%. The mixed phase activated gypsum has good activity. In the liquid phase wet-based state, the performance can remain stable for a long time, and it will not hydrate and agglomerate for 16-40 hours, which can reduce the scaling and agglomeration problems of the process filtration and transportation system; and a highly active building material product can be obtained after adding an activator. Mixed phase activated gypsum can be used directly as a wet-based product to process building materials, such as gypsum blocks, gypsum strips, paper-faced / non-paper-faced gypsum boards and other projects, which can achieve very low use costs; it can provide low-phosphorus and low-water raw materials in the acid production of phosphogypsum, reduce production energy consumption, and improve cement quality; it can also be dried into powder and then activated to process gypsum blocks, gypsum strips, gypsum-based self-leveling mortar and other products, which can replace construction gypsum on a large scale in the field of building materials.
[0030] 5. The process of this application makes comprehensive use of the waste heat generated, which saves energy and reduces emissions. The heat of dilution of concentrated sulfuric acid generates a high-temperature mixed acid liquid phase, which provides heat for adding the filtrate of the crystallization tank. At the same time, the low-temperature mixed acid liquid phase is added to the extraction tank. The extraction tank can reduce heat removal, reduce the load and investment of the device. This device saves the heat source required for heating the process and the energy consumption required for cooling. It is a two-way heat recycling process with significant energy-saving and emission-reduction effects.
[0031] 6. The recovery rate of phosphorus resources is greatly improved. The total phosphorus of the mixed phase activated gypsum is less than 0.2%, compared with the phosphorus of 0.8-1.5% in the traditional dihydrate phosphogypsum and hemihydrate phosphogypsum processes. This process not only obtains harmless gypsum products, but also recovers a large amount of phosphorus resources. This improved wet phosphoric acid process can increase the phosphorus recovery rate from 96% to more than 99%, achieving the strategic goal of rich ore mining. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further defined below in conjunction with specific implementation methods, but the scope of protection required is not limited to the description.
[0034] Example 1
[0035] (1) adding phosphate rock powder, concentrated sulfuric acid, low-temperature mixed acid H, and low-temperature crystallization filtrate F into a wet phosphoric acid extraction tank, wherein the mass ratio of phosphate rock powder: concentrated sulfuric acid: low-temperature mixed acid H, and low-temperature crystallization filtrate F is 1:0.5:2:1.5; the reaction temperature of the extraction tank is 80° C., and the reaction is carried out for 40 minutes to obtain a reaction slurry A; the phosphate rock used is Guizhou phosphate rock, with a phosphorus content of 31%, and the phosphate rock powder fineness is 90 mesh;
[0036] (2) The reaction slurry A in step (1) is subjected to solid-liquid separation to obtain solid B and clear liquid C, the clear liquid C is entered into the acid reservoir as the finished phosphoric acid, and the solid B is entered into the crystallization tank together with the high-temperature crystallization filtrate F, concentrated sulfuric acid, and a crystal form control agent; the temperature of the crystallization tank is controlled to be 90° C., and the crystallization is performed for 4 hours to obtain slurry D; the liquid-solid ratio of slurry D is 5:1, the P2O5% content is 7.6%, and the crystal form control agent content is 5.66%; the specific content of the crystal form control agent is: iron oxide content 0.36%, aluminum oxide 0.95%, magnesium oxide 1.85%, and fluorosilicic acid 2.50%
[0037] (3) performing solid-liquid separation on the slurry D in step (2) to obtain a solid phase E and a filtrate F, and washing the solid phase E with water to obtain a solid phase E and a washing liquid G. After the solid phase E is dried, it is a mixed phase activated gypsum;
[0038] (4) adding concentrated sulfuric acid to the washing liquid G in step (3) in a tubular reactor to dilute and release heat to obtain a high-temperature mixed acid H, and the high-temperature mixed acid H is heat exchanged to obtain a low-temperature mixed acid H which enters an extraction tank for recycling;
[0039] (5) The low-temperature crystallization filtrate F in step (3) enters a dedicated heat exchanger to obtain a high-temperature crystallization filtrate F, and the high-temperature crystallization filtrate F enters a crystallization tank for recycling.
[0040] The composition of the mixed phase activated gypsum obtained in Example 1 was tested, and the details are as follows:
[0041] According to GB / T 5484-2012 phosphomolybdenum blue spectrophotometry, the phosphorus in the product is tested, including total phosphorus: 0.17%, water-soluble phosphorus: 0.07%; according to GB / T 5484-2012 fluoride ion selective electrode method for determination of water-soluble fluorine: 0.06%; the "GB / T36141-2018" oven method was used to detect the three phases of gypsum. The composition of fresh gypsum just produced was 45.8% anhydrous phase, 27.3% semi-aqueous phase, 16.3% dihydrate phase, and 11.5% acid insoluble matter; wet-based fresh gypsum stability data: after natural placement for 18 hours, the three phases of gypsum were: 43.5% anhydrous phase, 30.1% semi-aqueous phase, 17.4% dihydrate phase, and 10.9% acid insoluble matter; mixed-phase gypsum excitation activity: 2 hours after the activator was added to the fresh gypsum, the three phases of gypsum changed to: 11.5% anhydrous phase, 3.3% semi-aqueous phase, 76.7% dihydrate phase, and 9.9% acid insoluble matter.
[0042] Example 2
[0043] (1) adding phosphate rock powder, concentrated sulfuric acid, low-temperature mixed acid H, and low-temperature crystallization filtrate F into a wet phosphoric acid extraction tank, wherein the mass ratio of phosphate rock powder: concentrated sulfuric acid: low-temperature mixed acid H, and low-temperature crystallization filtrate F is 1:0.2:2:1.5; the reaction temperature of the extraction tank is 80° C., and the reaction is carried out for 40 minutes to obtain a reaction slurry A; the phosphate rock used is Hubei phosphate rock, with a phosphorus content of 30%, and the phosphate rock powder fineness is 90 mesh;
[0044] (2) The reaction slurry A in step (1) is subjected to solid-liquid separation to obtain solid B and clear liquid C, the clear liquid C is entered into the acid reservoir as the finished phosphoric acid, and the solid B is entered into the crystallization tank together with the high-temperature crystallization filtrate F, concentrated sulfuric acid, and a crystal form control agent; the temperature of the crystallization tank is controlled to be 90° C., and the crystallization is performed for 4 hours to obtain slurry D; the liquid-to-solid ratio of slurry D is 5:1, the P2O5% content is 7.0%, and the crystal form control agent content is 5.52%; the specific content of the crystal form control agent is: iron oxide content 0.65%, aluminum oxide 1.10%, magnesium oxide 1.83%, and fluorosilicic acid 1.94%
[0045] (3) subjecting the slurry D in step (2) to solid-liquid separation to obtain a solid phase E and a filtrate F, and washing the solid phase E with water to obtain a solid phase G and a washing liquid H. The solid phase G is a mixed phase activated gypsum, and the wet-based product is used for online processing of gypsum products such as gypsum blocks, fiber gypsum boards, etc.;
[0046] (4) adding concentrated sulfuric acid to dilute the filtrate F in step (3) in a tubular reactor to release heat to obtain a high-temperature mixed acid H, and then the high-temperature mixed acid H is heat exchanged to obtain a low-temperature mixed acid H, which is then recycled into an extraction tank;
[0047] (5) The low-temperature crystallization filtrate F in step (4) enters a dedicated heat exchanger to obtain a high-temperature crystallization filtrate F, and the filtrate F enters a crystallization tank for recycling.
[0048] A simple test was conducted on the composition of the mixed-phase activated gypsum obtained in Example 2: the anhydrous phase accounted for 48.3%, the semi-aqueous phase accounted for 21.4%, the dihydrate phase accounted for 18.5%, and the acid-insoluble matter accounted for 11.3%; the total phosphorus of the product was 0.17%, the water-soluble phosphorus was 0.04%, and the water-soluble fluorine was 0.07%.
[0049] Example 3
[0050] (1) adding phosphate rock powder, concentrated sulfuric acid, low-temperature mixed acid H, and low-temperature crystallization filtrate F into a wet phosphoric acid extraction tank, wherein the mass ratio of phosphate rock powder: concentrated sulfuric acid: low-temperature mixed acid H, and low-temperature crystallization filtrate F is 1:0.1:3:0.8; the reaction temperature of the extraction tank is adjusted to 75° C., reacting for 50 minutes to obtain reaction slurry A; the phosphate rock used is Northeast phosphate rock, with a phosphorus content of 30%, and the phosphate rock powder fineness is 90 mesh;
[0051] (2) The reaction slurry A in step (1) is subjected to solid-liquid separation to obtain solid B and clear liquid C, the clear liquid C is entered into the acid reservoir as the finished phosphoric acid, and the solid B is entered into the crystallization tank together with the high-temperature crystallization filtrate F, concentrated sulfuric acid, and a crystal form control agent; the temperature of the crystallization tank is controlled to be 95° C., and the crystallization is performed for 3 hours to obtain slurry D; the liquid-solid ratio in slurry D is 3:1, the P2O5% content in the filtrate F is 14.0%, and the content of the crystal form control agent in the filtrate is 7.38%; the specific content of the crystal form control agent is: iron oxide content 2.51%, aluminum oxide 1.03%, magnesium oxide 2.17%, fluorosilicic acid 1.67%
[0052] (3) The slurry D in step (2) is subjected to solid-liquid separation to obtain a solid phase E and a filtrate F, and the solid phase E is washed with washing water to obtain a solid phase G and a washing liquid H. The solid phase G is the mixed phase activated gypsum, and the wet-based product is used for online processing of gypsum products such as fiber gypsum board, etc.;
[0053] (4) adding concentrated sulfuric acid to dilute the filtrate F in step (3) in a tubular reactor to release heat to obtain a high-temperature mixed acid H, and the high-temperature mixed acid H is heat exchanged to obtain a low-temperature mixed acid H which enters an extraction tank for recycling;
[0054] (5) The low-temperature crystallization filtrate F in step (4) enters a dedicated heat exchanger to obtain a high-temperature crystallization filtrate F, and the high-temperature crystallization filtrate F enters a crystallization tank for recycling.
[0055] A simple test was conducted on the composition of the mixed-phase activated gypsum obtained in Example 3: the anhydrous phase accounted for 58.5%, the semi-aqueous phase accounted for 21.0%, the dihydrate phase accounted for 11.1%, and the acid-insoluble matter accounted for 9.4%; the total phosphorus of the product was 0.19%, the water-soluble phosphorus was 0.08%, and the water-soluble fluorine was 0.05%.
[0056] Example 4
[0057] (1) adding phosphate rock powder, concentrated sulfuric acid, low-temperature mixed acid H, and low-temperature crystallization filtrate F into a wet phosphoric acid extraction tank, wherein the mass ratio of phosphate rock powder: concentrated sulfuric acid: low-temperature mixed acid H, and low-temperature crystallization filtrate F is 1:0.5:2:1.5; the reaction temperature of the extraction tank is 80° C., and the reaction is carried out for 40 minutes to obtain a reaction slurry A; the phosphate rock used is Guizhou phosphate rock, with a phosphorus content of 31%, and the phosphate rock powder fineness is 90 mesh;
[0058] (2) The reaction slurry A in step (1) is subjected to solid-liquid separation to obtain solid B and clear liquid C, the clear liquid C is entered into the acid reservoir as the finished phosphoric acid, and the solid B is entered into the crystallization tank together with the high-temperature crystallization filtrate F, concentrated sulfuric acid, and a crystal form control agent; the temperature of the crystallization tank is controlled to be 95° C., and the crystallization is performed for 6 hours to obtain slurry D; the liquid-to-solid ratio in slurry D is 3:1, the P2O5% content in the filtrate F is 13.6%, and the content of the crystal form control agent in the filtrate F is 5.91%; the specific content of the crystal form control agent is: iron oxide content 0.46%, aluminum oxide 0.90%, magnesium oxide 1.75%, and fluorosilicic acid 2.80%.
[0059] (3) performing solid-liquid separation on the slurry D in step (2) to obtain a solid phase E and a filtrate F, and washing the solid phase E with water to obtain a solid phase E and a washing liquid G. The solid phase E is the mixed phase activated gypsum, and the undried wet-based product is used as a raw material for acid production and cement co-production of phosphogypsum;
[0060] (4) adding concentrated sulfuric acid to the washing liquid G in step (3) in a tubular reactor to dilute and release heat to obtain a high-temperature mixed acid H, and the high-temperature mixed acid H is heat exchanged to obtain a low-temperature mixed acid H which enters an extraction tank for recycling;
[0061] (5) The low-temperature crystallization filtrate F in step (3) enters a dedicated heat exchanger to obtain a high-temperature crystallization filtrate F, and the high-temperature crystallization filtrate F enters a crystallization tank for recycling.
[0062] The composition of the mixed phase activated gypsum obtained in Example 4 was tested, as follows:
[0063] The anhydrous phase accounts for 59.5%, the semi-aqueous phase accounts for 26.6%, the dihydrate phase accounts for 4.1%, and the acid insoluble matter accounts for 9.4%; the total phosphorus of the product is 0.17%, the water-soluble phosphorus is 0.10%, and the water-soluble fluorine is 0.07%.
[0064] Finally, it should be pointed out that the above embodiments are only representative examples of the present invention. Obviously, the technical solution of the present invention is not limited to the above embodiments, and there are many variations. All variations that can be directly derived or associated with the content disclosed by ordinary technicians in this field should be considered as the protection scope of the present invention.
Claims
1. A method for producing mixed phase activated gypsum by wet phosphoric acid process, characterized in that: The specific steps include: (1) adding phosphate rock powder, concentrated sulfuric acid, low-temperature mixed acid, and filtrate to a wet phosphoric acid extraction tank; the mass ratio of phosphate rock powder: concentrated sulfuric acid: low-temperature mixed acid and filtrate is 1: (0-0.3): (1-5): (0.5-3); the reaction temperature of the extraction tank is adjusted to 50-90° C., reacting for 30-60 minutes, and obtaining phosphoric acid extraction slurry A; (2) subjecting the slurry A in step (1) to solid-liquid separation to obtain a solid phase B and a clear liquid C, wherein the clear liquid C enters the acid reservoir as the finished phosphoric acid, and the solid phase B enters the crystallization tank together with the high-temperature filtrate, concentrated sulfuric acid, and a crystal form control agent; controlling the temperature of the crystallization tank to 80-105° C., performing crystallization for 2-10 hours, and obtaining a slurry D; wherein the mass ratio of each component is: solid phase B: high-temperature crystallization filtrate F: concentrated sulfuric acid: crystal form control agent = 1: (0.8-5): (0.01-0.50): (0.01-0.6); (3) The slurry D in step (2) is subjected to solid-liquid separation to obtain a low-temperature crystallization filtrate F and a solid phase, and the solid phase is washed with washing water to obtain a solid phase E and a washing liquid G; the solid phase E is dried to obtain a mixed-phase activated gypsum or is directly used for subsequent gypsum product processing without drying.
2. The method according to claim 1, characterized in that: The fineness of the phosphate rock powder in step (1) is 80-100 mesh, and the P2O5 content contained therein is 10-40%.
3. The method according to claim 1, characterized in that The mass fraction of the concentrated sulfuric acid in step (1) is 93-98%.
4. The method according to claim 1, characterized in that The low-temperature mixed acid in step (1) has a sulfuric acid concentration of 40-70% and a P2O5% concentration of 0.5-5%. The low-temperature mixed acid H can be recycled or directly prepared.
5. The method according to claim 1, characterized in that The filtrate in step (1), wherein the P2O5% content is 3-16% and the crystal form control agent is 1.0-5.0%, can be recycled using the low-temperature crystallization filtrate F, or can be directly prepared.
6. The method according to claim 1, characterized in that The high-temperature filtrate in the step (2), wherein the P2O5% content is 3-16% and the crystal form control agent is 1.0-5.0%, can be obtained by using the low-temperature crystal transformation filtrate F to enter a dedicated heat exchanger to obtain the high-temperature crystal transformation filtrate F, or can be obtained by direct configuration.
7. The method according to claim 1, characterized in that The crystal form control agent is a combination of four components: iron oxide, aluminum oxide, magnesium oxide and fluorosilicic acid, and its total mass accounts for 2.0-8.0% of the crystal transformation filtrate components, wherein the content of iron oxide is 0.2-0.3%, aluminum oxide is 0.4-2.0%, magnesium oxide is 0.5-4.0%, and fluorosilicic acid is 0.9-4.0%.
8. The method according to claim 1, characterized in that The method further comprises the step (4): adding concentrated sulfuric acid to the washing liquid G in the step (3) in a tubular reactor to dilute and release heat to obtain a high-temperature mixed acid H; the high-temperature mixed acid enters a dedicated heat exchanger for heat exchange to obtain a low-temperature mixed acid H which enters an extraction tank for recycling.
9. The method according to claim 1, characterized in that: The method further comprises step (5): the low-temperature crystallization filtrate F of step (3) is fed into a dedicated heat exchanger to obtain a high-temperature crystallization filtrate F, and the high-temperature crystallization filtrate F is fed into a crystallization tank for recycling.
10. Use of the method according to any one of claims 1 to 9 in wet-process phosphoric acid.
Citation Information
Patent Citations
A method for preparing α - hemihydrate gypsum from dihydrate gypsum
CN105174760B